Effect of fermentation on bioactive compounds and structural properties of wheat bran - Nidhi Tiwari; Reshma Saroj; Mudasir Ahmad Malik; Devinder Kaur (Discover Food)
Abstract In the present study bran of two wheat cultivars (PBW-154 and HD-2967) was fermented for different time duration (24 h, 48 h and 72 h) and the effect of fermentation on the quantity of bioactive compounds in the bran and on the structure of bran were evaluated. Six bioactive compounds were detected in the bran of both wheat cultivars. These include p-hydroxybenzoic acid, syringic acid, vanillic acid, ferulic acid, p-coumaric acid and gallic acid. Among the bioactive compounds ferulic acid was found highest in the bran of both wheat cultivars while p-hydroxybenzoic acid was found lowest in the bran of PBW-154 variety and syringic acid was found lowest in the bran of HD-2967 variety. All the six bioactive compounds detected were increased after the fermentation for both the cultivars bran. Scanning electron microscopy shows the occurrence of loose networks of fibers tying with tissues and starch particles together and other granule structure that indicates the release of bound phenolic compound at 72 h of fermentation. Fermentation increased the crystallinity index because it hydrolyses the amorphous region. FTIR in yeast fermented wheat bran cultivar showed presence of OH elongation group, C = O bond –H stretching vibration bond. In fermented wheat bran the absorption bands between 29.18 cm−1 or 2850 cm−1associated with OH-OH elongation vibration.